Evaluasi Kebijakan Penanggulanan Bencana Banjir di Kecamatan Kasemen ( Studi pada Badan Penanggulangan Bencana Daerah Kota Serang) - Alya Rahmah; Dina Dwi Apriani; Meylani Wulandari; Reza Triyana; Siti Aminatul Zahro; Reza Damayanti (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to evaluate the implementation of flood disaster management policies in Kasemen Subdistrict by the Regional Disaster Management Agency (BPBD) of Serang City, particularly in response to the major flooding that occurred in early 2026. Geographically, Kasemen Subdistrict is a downstream area prone to annual flooding due to the confluence of the Cibanten River overflow and tidal flooding (rob). Based on preliminary research, several issues were identified in the field, such as insufficient pre-disaster mitigation outreach, low levels of community self-preparedness, and suboptimal distribution of quick-response aid during emergency response. To analyze these issues, this descriptive qualitative study was designed using William N. Dunn’s six-criteria policy evaluation framework, which includes effectiveness, efficiency, adequacy, equity, responsiveness, and appropriateness. Data collection was designed using direct observation, in-depth interviews with the Regional Disaster Management Agency (BPBD) and affected communities, and documentation. Through this approach, the research results are expected to map bureaucratic barriers, assess the alignment of Local Regulation No. 3 of 2021, and formulate comprehensive long-term strategic recommendations for disaster management in Serang City.